Bone Morphogenetic Protein Coating on Titanium Implant Surface: a Systematic Review - Haim Haimov; Natali Yosupov; Ginnady Pinchasov; Gintaras Juodzbalys (eJournal of Oral Maxillofacial Research)
Objectives: The purpose of the study is to systematically review the osseointegration process improvement by bone morphogenetic protein coating on titanium implant surface.